The Influence Of Brand Equity, Service Quality And Personal Selling On Customer Loyalty Through Customer Satisfaction (Case Study On Customers Of Garda Oto Motor Vehicle Insurance Products) - Septiadi Nugroho; Muchsin Saggaff Shihab (Jurnal Scientia, 2024)
The era of globalization promises business opportunities and challenges for all companies, the phenomenon of intense competition will increasingly direct the economic system to a market mechanism that positions marketers to always develop and seize market share. Through Garda Oto motor vehicle insurance products, PT Asuransi Astra Buana (Asuransi Astra) has succeeded in becoming one of the market leaders in the general insurance industry in Indonesia. One of the powerful weapons to achieve this success is to maintain customer satisfaction & loyalty, accompanied by brand equity, service quality and marketing strategies such as personal selling owned by the company. This study aims to determine the effect of brand equity, service quality and personal selling on customer loyalty through customer satisfaction on Garda Oto motor vehicle insurance products. This type of research is quantitative research. The data presented in this study were obtained through questionnaires distributed to 142 respondents. Statistical analysis using the SEM PLS method to test the model and hypothesis. The results of this study indicate that brand equity has a positive and significant effect on customer loyalty, brand equity does not have a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, personal selling has no positive and significant effect on customer loyalty, personal selling has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, brand equity has no positive and significant effect on customer loyalty through customer satisfaction, service quality has a positive and significant effect on customer loyalty through customer satisfaction and personal selling has a positive and significant effect on customer loyalty through customer satisfaction.